Effect on Concrete Strength Due to Partial Replacement of Cement by Rice Husk Ash (Technical Journal, 2025)
Concrete is well known as a heterogeneous mix of cement, water, and aggregates. Various materials are added to obtain concrete of the desired property. Rice husk ash is the byproduct of burned rice husk at higher temperatures and is commonly used nowadays to improve the mechanical properties of concrete. The main objective of this Research is to study the suitability of the RHA (both blue ignition and yellow ignition brunt Rice husk ash) as a pozzolanic material for cement replacement in concrete. However, it is expected that the use of RHA in Concrete improves the strength property of concrete. Also, it is made to develop the concrete using rice husk ash as a source material for partial replacement of cement which satisfies the structural properties of concrete like compressive strength. In this study IS code was considered for the test of material and concrete and compare with code. It provides several advantages, such as improved strength and durability properties and environmental benefits related to the disposal of waste materials and to reduce carbon dioxide emissions. Up to now, little research has been done to investigate the use of RHA as a supplementary material in cement and concrete production. The compressive strength of RHA concrete studied shows that the maximum compressive strength can be found for a mix with 5 to 15 percent of RHA in both blue ignition and yellow ignition brunt Rice husk ash, beyond this value, the strength goes on decreasing for all age of concrete.